The Compressive Strength of Adobe Block Masonry Walls - Vilane, B. R. T.; Hann, M. J. (European Journal of Applied Sciences, 2022)
Masonry is a composite material that is fabricated using natural and/ or artificial units that are joined together with mortar. The natural units include stone amongst others, while the artificial includes bricks and blocks that could be made out of concrete or fired clay products as well as adobe (stabilised or unsterilized). The wide spectrum of the units used in masonry wall fabrication demands that appropriate tests should be conducted to determine their compressive strength and by extension the effectiveness of the wall masonry in performing its inherent architectural design functions of the building such as environmental protection of its inhabitants. An experiment was conducted (i) to determine the structural suitability of stabilised adobe block masonry under uniform and concentrated loading and (ii) to determine adobe block masonry design guidelines. All block units for the test masonry were fabricated using the appropriate Portland cement: sand mix of 1: 11 identified using mix trials for the adobe block categories that were greater than 11.1 N/mm2. The concrete mix was prepared using a concrete mixer and moulded. Moulding was conducted using modified standard 6-inch adobe block mould that led to a 300 mm x 150 mm x 100 mm block. The blocks were cured for seven days under polythene sheets. There were two sets of masonry tests running in parallel; (1) the compressive strengths of the simulated stabilised adobe block masonry under uniformly distributed loads (prism tests) with three different mortar regimes; weak (1:8), medium (1:5) and strongest (1:3) and (2) masonry characteristic compressive strengths under concentrated loads (wall tests) using only the medium mortar mix (1:5). Prism specimens (300 mm x 150 mm x 460 mm) and wall specimen (920 mm x 150 mm x 460 mm) had three replications and cured under laboratory ambient environment conditions for 28 days prior to testing. Test specimens were subjected to compression under uniaxial uniformly distributed loads applied vertically and continuously at a rate of 1 N/mm2/minute to failure. There were 3 wall tests running parallel for each of the 4 block Portland cement proportions at the 1:5 mortar mixes. Data were analysed using MS Excel featuring descriptive statistics. Confidence intervals (95%) using the Student t-test were used to compare variations between and within specimens. Vertical deformations and time to failure were analysed using video tapes through Daub 2.0, video editing free download software. The results indicated that with the prism tests the increase in Portland cement masonry block proportion from 5% - 15% (3.0 N/mm2 - 15.4 N/mm2) significantly increased the masonry characteristic compressive strength at all mortar compressive strengths. However, the masonry characteristic compressive strengths were significantly less than that of the corresponding block. This trend was similar to the wall tests. At high block and low mortar compressive strengths, prism failure was initially by vertical tensile cracking through the mortar followed by the block, whereas at high masonry block and mortar strengths, failure was sudden and typically manifested by initial vertical tensile cracking and eventually side splitting of the block and mortar.Wall failure at low concentrated loads, was initially manifested by vertical cracks along the joint directly below the load point, and at its edges on both sides of the wall. The proposed design guidelines for stabilised adobe block masonry included mortar designations (a), (b) and (c) with masonry mortar proportions by volume (cement: sand) of 1:3, 1:5, and 1:8, respectively, under uniform and concentrated loads were proposed for use in adobe block masonry for agricultural structures.